Abundance, genetic diversity and sensitivity to demethylation inhibitor fungicides of Aspergillus fumigatus isolates from organic substrates with special emphasis on compost. Issue 12 (14th August 2017) - Santoro, Karin; Matić, Slavica; Gisi, Ulrich; Spadaro, Davide; Pugliese, Massimo; Gullino, Maria L
Abstract: BACKGROUND: Aspergillus fumigatus is a widespread fungus that colonizes dead organic substrates but it can also cause fatal human diseases. Aspergilloses are treated with demethylation inhibitor (DMI) fungicides; however, resistant isolates appeared recently in the medical and also environmental area. The present study aims at molecular characterizing and quantifying A. fumigatus in major environmental habitats and determining its sensitivity to medical and agricultural DMI fungicides. RESULTS: A. fumigatus was isolated only rarely from soil and meadow/forest organic matter but high concentrations (10 3 to 10 7  cfu/g) were detected in substrates subjected to elevated temperatures, such as compost and silage. High genetic diversity of A. fumigatus from compost was found based on SSR markers, distinguishing among fungal isolates even when coming from the same substrate sample, while subclustering was observed based on mutations in cyp51A gene. Several cyp51A amino acid substitutions were found in 15 isolates, although all isolates were fully sensitive to the tested DMI fungicides, with exception of one isolate in combination with one fungicide. CONCLUSION: This study suggests that the tested A. fumigatus isolates collected in Italy, Spain and Hungary from the fungus' major living habitats (compost) and commercial growing substrates are not potential carriers for DMI resistance in the environment. © 2017 Society of Chemical Industry